Alat Permainan Edukasi (APE) Meningkatkan Perkembangan Motorik Halus pada Anak Usia 4-6 Tahun - Mirna Lisa; Ani Mustika; Neneng Siti Lathifah (Politeknik Kesehatan Tanjung Karang, 2020)
Games that are available today do not all contain elements of education that can help children's brain growth. Choosing educational toys that educate children today is indeed not easy. Based on a preliminary survey on January 10, 2019, conducted at Al-Kautsar Kindergarten out of 10 mothers, it was found that 6 (60%) mothers who gave playing equipment were not based on educational play equipment for their children and 4 (40%) mothers who gave toys to their children based on tools educational game to his child. Hypothesis there is the effect of giving APE to the development of fine motor children in 4-6 years. This type of quantitative research is quasi-experimental design with one group pretest and posttest design. The population of children in Al-Kautsar Kindergarten is 150 people, a sample of children aged 4-6 years in Al-Kautsar Kindergarten is 51 people. Sampling technique with accidental sampling. Dependent Research Variables Educational Game Tools and Independent Variables are Fine Motor Development. The time of this research is 4 months. The method used starts from pretest about fine motor skills of children and then carried out with interventions with 10 indicators and posttest. The results obtained are the effect of providing Educational Tools to children aged 4-6 years in Kindergarten AL-Kautsar with p-value 0,000 so it is smaller than the p-value of α (<0,005).